Mechanisms of Compensation of the Driver’s Sense of Dimensions - Lobanova, Yuliia I. (Journal of Intellectual Disability - Diagnosis and Treatment, 2019)
The research paper analyzes the peculiarities of training candidates for drivers for certain subtypes (components) of combined driving. The work is focused on the analysis of opportunities to improve the quality of training of drivers for such subtypes of driving as orientation on the road, which, in particular, is the basis for mastering parking manoeuvres. Based on the analysis of a number of works, less confidence of women in driving a vehicle in a limited space (as opposed to men) is shown, which is manifested in the choice of simpler tasks for this subtype of activity. The psychological nature of the sense of dimensions is analyzed, the importance of visual sensations and long-term memory for the formation and development of this feeling is shown. The hypothesis about the possibility of compensating for the insufficiently developed and worsening with age sense of dimensions due to reliance on visual figurative memory and subject reflection is formulated. The results of the empirical study, which found the relative independence of the level of development of linear and angular eye estimation and confidence in parking with different driving experience, are presented. The results of the analysis of the tasks for reflection of driving in a limited unstructured space by 100 drivers are presented, which confirm the hypothesis of the study: visual landmarks for parking in non-standard conditions, in percentage terms, are more often identified by older drivers with longer experience but with poorer indicators of linear and angular eye estimation, being no different in terms of parking confidence from young drivers with better eye estimation, which can be considered as a manifestation of the compensation mechanism.